Shear behaviour of high-strength concrete beams - He, Lihua. (2008)
The rapidly increasing use of high strength concrete as an alternative to the more classical materials (normal strength concrete) requires knowledge by the design engineer of HSC behaviour in shear. The experimental investigation conducted in this project is important to evaluate the current design methods used for shear design of HSC beams, and the theoretical model proposed in this research for reinforced concrete element is capable of predicting not only the ultimate shear strength but also the load-deformation response of concrete elements subjected to in-plane shear and normal stresses.